2022
DOI: 10.3390/app12073549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diesel Hydrocarbon Components on Cetane Number and Engine Combustion and Emission Characteristics

Abstract: Commercial diesel consists of hundreds of hydrocarbons such as alkanes, cycloalkanes, and aromatics. The components of the fuel’s composition are what determine its physical and ignition properties, and their variations affect engine performance. In this study, n-heptane, n-dodecane, tetralin, and decalin were chosen as typical additives to blend with commercial diesel according to the China VI standard (Heavy Duty Diesel Vehicle Pollutant Emission Limits and Measurement Methods) in 20% and 50% volume fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Unlike spark ignition engines, efficient combustion in a diesel engine requires reactive hydrocarbon mixtures with short ignition delays . The ignition delay of hydrocarbons is directly related to their structure in the following order: normal alkanes < branched alkanes ∼ cycloalkanes < aromatic compounds. , A key metric of diesel fuel quality is the cetane number, which is inversely proportional to the ignition delay, and proportional to the number of consecutive methylene groups in a hydrocarbon chain. For example, decane has a higher cetane number than nonane, which is higher than octane, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike spark ignition engines, efficient combustion in a diesel engine requires reactive hydrocarbon mixtures with short ignition delays . The ignition delay of hydrocarbons is directly related to their structure in the following order: normal alkanes < branched alkanes ∼ cycloalkanes < aromatic compounds. , A key metric of diesel fuel quality is the cetane number, which is inversely proportional to the ignition delay, and proportional to the number of consecutive methylene groups in a hydrocarbon chain. For example, decane has a higher cetane number than nonane, which is higher than octane, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of CO emitted for the gasoline samples across the randomly selected camps ranged between 78. [45,46]. The higher components are less volatile and difficult to combust at low temperatures and within a short combustion period [45].…”
Section: Quantified Emissions From the Use Of Artisanal Gasolinementioning
confidence: 99%
“…[45,46]. The higher components are less volatile and difficult to combust at low temperatures and within a short combustion period [45]. Some of the heavy compounds that were not completely oxidized are emitted as carbon (II) oxide and other components which escape burning are released as hydrocarbon, either in the form of volatile organics or as fly ash (i.e.…”
Section: Quantified Emissions From the Use Of Artisanal Gasolinementioning
confidence: 99%
“…In a study [ 21 ], literature conducted hydrogen doping experiments in a ZS1100 single-cylinder engine and demonstrated that hydrogen doping can effectively reduce overall fuel consumption in a diesel engine at low loads. The engine hydrogen doping experiments in the literature [ 22 ] show that the addition of hydrogen reduces exhaust emissions and stabilizes the combustion process and performance of the diesel engine under excessive operating conditions. These studies have shown that hydrogen doping into conventional fuel engines can affect the combustion performance of the engine, and that the right amount of hydrogen doping can reduce overall fuel consumption and minimize exhaust emissions.…”
Section: Introductionmentioning
confidence: 99%